UR_GERICHTE 2015_OG V 14 37. vom 14. April 2015 - UR Obergericht (2015)
Kommunale Steuern. Art. 5 Abs. 2, Art. 8 Abs. 1, Art. 26, Art. 27, Art. 50 Abs. 1, Art. 127 Abs. 2 und 3 BV. Art. 51 Abs. 1, Art. 52, Art. 59 Abs. 1 lit. a und Abs. 3, Art. 60 Abs. 1 und 2, Art. 106 Abs. 1 und Art. 107 Abs. 1 KV.